Chinese Urban Shi-nema - Fleming, David H. author. aut Link
XVIII, 235 p. 40 illus. in color.
Keywords: This book dives into the mise-en-scène of contemporary China to explore the “becoming cinema” of Chinese cities, societies, and subjectivities. Set in the wake of China’s radical and rapid period of urbanization and infrastructural transformation, and situating itself in the processual city of Ningbo, the book combines empirical, ficto-critical, and philosophical methods to generate a dynamic account of everyday life as new forms of consumer culture bed in. Harnessing a Realist approach that allows for different scales of analysis, the book zooms in on five architectural assemblages including: surreal real estate showrooms; a fragmented history museum; China’s “first and best” Sino-foreign university; a new “Old town”; and weird gamified “any-now(here)-spaces.” Together these modern arrangements and machines for living cast light upon the broader picture sweeping up greater China. .